2022
DOI: 10.15517/am.v34i1.50301
|View full text |Cite
|
Sign up to set email alerts
|

¿La palma aceitera (Elaeis guineensis) genera un impacto negativo sobre el suelo? Una revisión

Abstract: Introducción. La palma de aceite (Elaeis guineensis) es uno de los monocultivos perennes que se ha extendido a casi un poco más de diecinueve millones de hectáreas en el mundo, su expansión ha generado debate social, económico y político en diversos países tropicales. Una de las problemáticas que se ha discutido, es el impacto sobre las propiedades fisicoquímicas, biológicas y ecológicas del suelo. Objetivo. (i) Ofrecer un panorama actual de la expansión del cultivo de palma de aceite para una zona de la regió… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Studies suggest that the association of crops with oil palm is complicated since the canopy cover transmits little light to the soil surface, which makes it impossible for other commercial plants to grow and develop [ 11 ]. In addition, roots become entwined, causing soil compaction, nutrient competition, and strangulation of the crop roots [ [12] , [13] , [14] ]. However, it has been reported that oil palm included in an agroforestry system improves the physicochemical and biological properties of the soil, reduces carbon loss, and increases family income, among others [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that the association of crops with oil palm is complicated since the canopy cover transmits little light to the soil surface, which makes it impossible for other commercial plants to grow and develop [ 11 ]. In addition, roots become entwined, causing soil compaction, nutrient competition, and strangulation of the crop roots [ [12] , [13] , [14] ]. However, it has been reported that oil palm included in an agroforestry system improves the physicochemical and biological properties of the soil, reduces carbon loss, and increases family income, among others [ 15 ].…”
Section: Introductionmentioning
confidence: 99%